Peningkatan Kualitas Bungkil Inti Sawit Dengan Fermentasi Terhadap Aktivitas Enzim Dan Kandungan Zat Makanan - Mirnawati Mirnawati (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2007)
The present work was aimed to study the effect of temperature and time of incubation of palm kernel cake fermented with A. niger on the activity of enzymes and nutrient content. The experiment was arranged in completely factorial design of 3x3 patterns. The first factor was three levels of temperature of 30, 37, 41oC, the second were three different times of incubation of 4, 6, and 8 days. Parameter observed included cellulose and protease activities, crude protein and crude fiber contents. Results showed that there was a signifficantly interaction between temperature and incubation times (P< 0,01) on enzyme activity of cellulose and protease and crude protein, but time of fermented were significantly (P<0,05) on crude fiber of palm kernel cake fermentation. It was concluded that the optimum temperature and time of incubation were 30 oC and 6 day, which gave the highest content of crude protein (27,70 %) and crude fiber (17.73 %).